Case Report: Good Prognosis of Mixed Alien Hand Syndrome by Verbal-Cue Rehabilitation Exercise - Qu, Kang; Gan, Lin; Jiang, Wei; Yu, Peng; Dong, Ming (Frontiers in Neurology, 2021)
Mixed alien hand syndrome is a rare disease reported in the literature. The mixed callosal-frontal variant of alien hand syndrome is associated with uncoordinated hand movements, and patients may present with an involuntary grasp reflex and intermanual conflict. There are few videos in the existing literature on the comparison of patients’ condition before and after recovery of the symptoms of mixed alien hand syndrome. We presented the prognosis of mixed alien hand syndrome in the form of a video. In addition, we have included some videos on the comparison of patients’ condition before and after recovery of the symptoms of mixed alien hand syndrome. A 57-year-old woman presented with left-handed intermanual conflict and right-handed involuntary grasp reflex due to infarction of the frontal lobe and corpus callosum. She was diagnosed with a mixed callosal-frontal variant of alien hand syndrome. Her left hand counteracted the purposeful movements of the right hand. However, the intermanual conflict disappeared after 3 months of therapy, including drug treatment and verbal-cue rehabilitation, and she regained normal coordination of her hand movements. Her prognosis was good despite the large corpus callosum lesions. The patient’s uncoordinated hand movements affected her daily life and caused psychological problems. Initiating rehabilitation early was important and necessary for her to regain coordination. It is possible that the verbal-cue training method played an important role in the patient’s recovery. Therefore, this method of rehabilitation method deserves consideration and can be adopted in larger cohort studies as we presented only a single case. The possible mechanisms behind the verbal-cue exercise require further studies. And this patient had a good prognosis despite severe corpus callosum injury, which may merit further investigation.